2007
DOI: 10.1093/intqhc/mzl073
|View full text |Cite
|
Sign up to set email alerts
|

Patient, carer and staff experience of a hospital-based stroke service

Abstract: Some of the patients' and carers' perspectives have not been previously reported in the stroke literature, including a desire for individualized treatment, the consideration of wider, non-physical needs and the carers' sense of burden. In addition, the study revealed how staff, carers and patients viewed each other and the service and demonstrated the concordance of their perceptions. However, staff showed little insight into the users' need for information and negative experiences of care. In contrast with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 23 publications
(26 reference statements)
10
81
1
Order By: Relevance
“…Such themes have been observed in the stroke carer literature, including the role of information in improving carers' knowledge of stroke and their satisfaction with treatment. 6,7 Our fi ndings were particularly consistent with those of Cameron et al, 7 who found that health care providers struggled with decisions about how and when to deliver stroke-related information to carers. Similarly, our participants identifi ed challenges with information provision, most notably related to the timing and amount of information provided.…”
Section: Informationsupporting
confidence: 87%
See 3 more Smart Citations
“…Such themes have been observed in the stroke carer literature, including the role of information in improving carers' knowledge of stroke and their satisfaction with treatment. 6,7 Our fi ndings were particularly consistent with those of Cameron et al, 7 who found that health care providers struggled with decisions about how and when to deliver stroke-related information to carers. Similarly, our participants identifi ed challenges with information provision, most notably related to the timing and amount of information provided.…”
Section: Informationsupporting
confidence: 87%
“…These fi ndings are congruent with research acknowledging the roles of different disciplines in supporting carers' changing needs. 7 Similar to fi ndings by Morris, Payne, and Lambert, 6 participants in this study highlighted concerns around availability of care on the wards and the impact this might have on the ability to provide supports to carers and patients. Participants emphasized discharge home as a crucial stage for supporting carers.…”
Section: Summary Of Main Fi Ndingssupporting
confidence: 69%
See 2 more Smart Citations
“…There was confusion about the roles of agencies and services and a lack of knowledge about voluntary support groups. Another study using focus groups about information needs after stroke found that lack of individual information about stroke and about discharge led to anxiety and problems with adjustment post-discharge (Morris, Payne and Lambert, 2007).…”
Section: Information Needs Of People With Strokementioning
confidence: 99%